Preserving the Archipelago's Heritage: Indonesian Cultural Program for Children of Indonesian Migrant Workers in Malaysia - Iman Ahmad Gymnastiar; Desi Destiana Agusman; Siti Nur Azizah (Universitas Muhammadiyah Purwokerto, 2025)
This community service activity explores how education by introducing Indonesian culture in Malaysia strengthens their cultural identity. With globalization threatening local identities, children of Indonesian Migrant Workers (PMI) often struggle to balance their home culture with their new environment. This community service activity found that integrating arts and culture into learning can deepen children’s connection to their heritage. Traditional songs effectively taught cultural values and fostered pride in Indonesian identity. This community service activity emphasizes the importance of culture-based education in preserving the identity of marginalized children in a foreign country.